2022
DOI: 10.1364/ol.472691
|View full text |Cite
|
Sign up to set email alerts
|

Label-free deep-UV microscopy detection and grading of neutropenia using a passive microfluidic device

Abstract: Neutropenia is a condition comprising an abnormally low number of neutrophils, a type of white blood cell, which puts patients at an increased risk of severe infections. Neutropenia is especially common among cancer patients and can disrupt their treatment or even be life-threatening in severe cases. Therefore, routine monitoring of neutrophil counts is crucial. However, the current standard of care to assess neutropenia, the complete blood count (CBC), is resource-intensive, time-consuming, and expensive, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Our method is both fast and efficient, capable of imaging and analyzing a 1mm X 2mm area (containing ¿20,000 cells) in approximately 3 minutes. Our automated analysis framework and low-cost microscope can be integrated with a microfluidic device 23 to create a single-wavelength-based, compact, automated point-of-care hematology analyzer that is well-suited for point-of-care, low-resource, at-home, and clinical settings, and will form part of future work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our method is both fast and efficient, capable of imaging and analyzing a 1mm X 2mm area (containing ¿20,000 cells) in approximately 3 minutes. Our automated analysis framework and low-cost microscope can be integrated with a microfluidic device 23 to create a single-wavelength-based, compact, automated point-of-care hematology analyzer that is well-suited for point-of-care, low-resource, at-home, and clinical settings, and will form part of future work.…”
Section: Discussionmentioning
confidence: 99%
“…Deep ultraviolet microscopy (UV) is a label-free imaging technique that relies on the characteristic spectral properties of endogenous biomolecules in this region of the spectrum (200-400 nm) to yield quantitative molecular and structural information from biological samples. 16,17,18,19,20,21,22,23,24 Deep-UV microscopy offers a higher spatial resolution than conventional methods because of the shorter wavelength of UV light. In addition, deep-UV microscopy enables contiguous imaging of live cells over long durations (> 6 hrs) without significant photodamage.…”
Section: Introductionmentioning
confidence: 99%
“…The requirements for preparing blood smears and searching for monolayer regions of blood smears for cell imaging may impede the device's applications by an untrained user. In our future study, we plan to combine the reported passive microfluid device 60 with our miniature microscope to improve and simplify the reported mobile blood analysis technique. In this manner, blood analysis can be performed by loading a drop of blood into a microchannel without requiring blood smears.…”
Section: Discussionmentioning
confidence: 99%
“…Deep-ultraviolet (UV) microscopy enables label-free, high-resolution, quantitative molecular imaging by leveraging unique absorption properties of biomolecules, such as nucleic acids, in the UV region of the spectrum (200-400nm) [5][6][7][8]. Recently, it has been demonstrated for fast hematology analysis of whole blood smears and blood samples in custom microfluidic cartridges for point-of-care applications enabled by advancements in low-cost UV LEDs and sensors [9][10][11][12][13]. UV microscopy has also been used for multi-spectral, label-free histopathology of tissue samples [14][15][16].…”
Section: Introductionmentioning
confidence: 99%